Experimental Study of The Effect of Addition of Calming Section on The Heat Transfer Process In A Uniformly Heated Inclined Tube - Nasser F. Hussain; Abdulhassan A. Karamallah; Akeel A. Mohammed (Engineering and Technology Journal, 2010)
Experimental research has been conducted for combined convection to study the local and average heat transfer for hydrodynamically fully developed (the value of L/D of calming section was 22.2) and thermally developing laminar air flow in a uniformly heated inclined tube. The study covered a wide range of Richardson number (Ri) from 0.08 to 2.5, Reynolds number from (518 to 2041), and Rayleigh number from (2.4~105to 3.9~105), with different angles of inclination {ƒ¿= 00 (horizontal), }300, }600, }900 (vertical)} where the minus sign refers to opposing flow and plus sign refers to aiding flow. An empirical correlations were made for the average Nusselt number as a function of Rayleigh number and Reynolds number for all angles of tube inclinationand compared with another correlations from previous works. Results show that the heat transfer process for low Richardson number is better than that for high Richardson number and the values of average Nusselt number (Nu ) increase as Peclet number (Pe) increases for the same Rayleigh number.